2018
DOI: 10.1177/1024907918798997
|View full text |Cite
|
Sign up to set email alerts
|

Hong Kong Poison Information Centre: Annual report 2017

Abstract: Objectives: To report and analyse the poisoning data of Hong Kong Poison Information Centre in 2017. Methods: In 2017, all poisoning cases received by Hong Kong Poison Information Centre were retrieved from its database (Poison Information and Clinical Management System) for analysis. Results: A total of 3956 poisoned cases were analysed. There were 1789 male patients (45.2%), 2159 female patients (54.6%) and 8 sex-unspecified patients (0.2%). The majority of cases (59.9%) were between 20 and 59 years old. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 13 publications
0
8
1
Order By: Relevance
“…A local review from the Hospital Authority of Hong Kong on 52 cases of Aconitum poisoning from 2004 to 2009 suggested that overdosing is the major underlying cause of poisoning [ 114 ]. There were five recent cases of aconite poisoning from 2016 to 2017, that the patients received medication from the Chinese Medicine Centre of Hospital Authority [ 115 ]. They were dispensed with normal doses of processed Fuzi but appeared to have symptoms from mild numbness to hypotension.…”
Section: Discussionmentioning
confidence: 99%
“…A local review from the Hospital Authority of Hong Kong on 52 cases of Aconitum poisoning from 2004 to 2009 suggested that overdosing is the major underlying cause of poisoning [ 114 ]. There were five recent cases of aconite poisoning from 2016 to 2017, that the patients received medication from the Chinese Medicine Centre of Hospital Authority [ 115 ]. They were dispensed with normal doses of processed Fuzi but appeared to have symptoms from mild numbness to hypotension.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the risk of poisoning is likely to be higher in girls. According to the public data, the reported incidence of poisoning (all causes) in females aged between 5 and 18 years is higher than for males in that age group (0.07% vs 0.04%) [ 37 , 38 ]. Additionally, sex differences in ADHD symptom severity may differ.…”
Section: Discussionmentioning
confidence: 99%
“…X-ray with arrows showing “lead lines” ( C ). Reprinted from ( A )—[ 94 ], ( B )—[ 95 ], ( C )—[ 96 ].…”
Section: Leadmentioning
confidence: 99%